The Effects of Commitment to Moral Self-improvement and Religiosity on Ethics of Business Students - Kurpis, Lada V. (Journal of business ethics, 2008)
Using survey methodology we examined the relationships between commitment to moral self-improvement (CMSI), religiosity, ethical problem recognition, and behavioral intentions in a sample of 242 business students. Results of the study suggest that CMSI predicts ethical problem recognition and behavioral intentions. Our findings also suggest that CMSI is positively related to religiosity. The study provides some evidence of CMSI being a mediator in the influence of religiosity on ethical problem recognition and behavioral intentions. Compared to religiosity, CMSI turned out to be a better predictor of perceived importance of ethics, ethical problem recognition, and ethical behavioral intentions. The results of the study have implications for increasing understanding of ethical decision-making, future studies of business ethics, and business ethics education.